Tunable Co3O4 hollow structures (from yolk–shell to multi-shell) and their Li storage properties. Issue 25 (15th June 2017) - Yin, Jingzhou; Zhang, Yu; Lu, Qingyi; Wu, Xinglong; Jiang, Zhengjing; Dang, Liyun; Ma, Haifeng; Guo, Yuanyuan; Gao, Feng; Yan, Qingyu
Abstract : In this work, we report a facile approach to synthesize uniform Co3 O4 hollow spheres with tunable shell numbers via controllably annealing cobalt(ii ) complex precursors at different heating rates. Abstract : In this work, we report a facile approach to synthesize uniform Co3 O4 hollow spheres with tunable shell numbers via controllably annealing cobalt(ii ) complex precursors at different heating rates. When evaluated as anodes for LIBs, the multi-shelled Co3 O4 spheres exhibit high specific capacity, good rate capabilities and excellent cycling stability (1058 mA h g −1 over 100 cycles at 1 A g −1 ).